2020
DOI: 10.7759/cureus.7435
|View full text |Cite
|
Sign up to set email alerts
|

Lateral External-fixation Adjacent to Radial Nerve

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…By using proper antibiotic therapy and wound management, several studies have demonstrated that the risk of infection in intramedullary nailing and external fixation has no difference [ 14 , 15 ]. External fixation could be used as a treatment option for our patient, but the treatment strategy we applied had several advantages; including, better wound management, absence of pin tract infection, and patient comfort [ 16 ]. On the other hand, the safe zone of the proximal pin of external fixator was comminuted in our patient that could fail the successful use of an external fixator [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using proper antibiotic therapy and wound management, several studies have demonstrated that the risk of infection in intramedullary nailing and external fixation has no difference [ 14 , 15 ]. External fixation could be used as a treatment option for our patient, but the treatment strategy we applied had several advantages; including, better wound management, absence of pin tract infection, and patient comfort [ 16 ]. On the other hand, the safe zone of the proximal pin of external fixator was comminuted in our patient that could fail the successful use of an external fixator [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…External fixation could be used as a treatment option for our patient, but the treatment strategy we applied had several advantages; including, better wound management, absence of pin tract infection, and patient comfort [ 16 ]. On the other hand, the safe zone of the proximal pin of external fixator was comminuted in our patient that could fail the successful use of an external fixator [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Safety of lateral-to-medial screws in the distal humerus has been described. 6,7 Risks of this approach include injury to the radial nerve and intraarticular breach of implants. Based on cadaveric studies, there are two areas of safety for placement of hardware percutaneously in order to avoid injury to the radial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal safe zone exists from approximately 14.8 cm proximal to the lateral epicondyle to 5 cm distal to the acromion. 6 However, the distal zone is the area of focus in this study. The traditional safe zone in adults, as described by Gerwin et al, is based on the finding that the radial nerve crosses the intermuscular septum approximately 10 cm proximal to the lateral epicondyle and then becomes an anterior structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation